Dimensional reduction upon calcium incorporation in Cs0.3(Ca0.3Ln0.7)PS4 and Cs0.5(Ca0.5Ln0.5)PS4. Issue 4 (21st December 2020) - Klepov, Vladislav V.; Kocevski, Vancho; Besmann, Theodore M.; zur Loye, Hans-Conrad
Abstract : A series of Ca-containing lanthanide thiophosphates has been obtained and their structural evolution from 3D for LnPS4 and Cs0.3 (Ln0.7 Ca0.3 )PS4 to 2D in Cs0.5 (Ln0.5 Ca0.5 )PS4 was shown as a function of Ca content. Abstract : Two series of new lanthanide thiophosphates with partial Ca occupancy of the Ln sites, Cs0.3 (Ca0.3 Ln0.7 )PS4 (Ln = Ce, Pr, Nd, Sm, Gd, Tb, and Dy) and Cs0.5 (Ca0.5 Ln0.5 )PS4 (Ln = Pr, Nd, Sm, Gd, and Tb), were synthesized using a CsI flux and structurally characterized. The first series with an idealized formula of Cs0.3 (Ca0.3 Ln0.7 )PS4 crystallizes in the R 3̄ m space group and belongs to a new structure type that consists of a channel containing [(Ca0.3 Ln0.7 )PS4 ] 0.3− framework, where the channels are occupied by severely disordered Cs + cations. A second new series with formula Cs0.5 (Ca0.5 Ln0.5 )PS4 crystallizes in the monoclinic C 2/ c space group and exhibits a layered structure consisting of [(Ca0.5 Ln0.5 )PS4 ] 0.5− layers with Cs + cations located between the layers for charge balance. Together with the parent structure type, LnPS4, these three structure types illustrate how the LnPS4 structure changes with Cs + cation incorporation, reducing its dimensionality from 3D to 2D. The magnetic properties of Cs0.3 [(Ca0.3 Ce0.7 )PS4 ] and Cs0.3 [(Ca0.3 Pr0.7 )PS4 ] were studied and revealed no magnetic transition down to 2 K.